Refugee child : my memories of the 1956 Hungarian revolution - Kalman, Bobbie (Crabtree Pub. Co., 2006)
"Refugee Child" is the compelling story of children's author Bobbie Kalman's experiences as a young girl during the Hungarian Revolution in 1956. A touching roller coaster ride of emotions, Kalman writes her story from the perspective of a nine-year-old. She relives both her frightening experiences as well as some warm, and even funny, memories of her family and their flight to freedom.